2019
DOI: 10.1111/mpp.12882
|View full text |Cite
|
Sign up to set email alerts
|

Haustoria – arsenals during the interaction between wheat and Puccinia striiformis f. sp. tritici

Abstract: SummaryAs an obligate parasite, Puccinia striiformis f. sp. tritici (Pst) forms haustoria to obtain nutrients from plant cells for development, and these structures are essential for pathogen survival. To better understand the contribution of haustoria to the interactions with the host plants, we isolated haustoria from susceptible wheat leaves infected with Pst race CYR31 and sequenced their transcriptome as well as those of urediospores and germ tubes, and compared the three transcriptomes. A total of 3524 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 46 publications
(60 reference statements)
2
35
0
Order By: Relevance
“…This pathogen possesses the ability to generate several resistance-breaking races or pathotypes that carry different race-specific avirulence or effector coding genes that make them more specialized in infecting different wheat cultivars. Pst genomes are highly heterozygous and encode several effectors (Chen et al, 2009(Chen et al, , 2010Cantu et al, 2013;Zheng et al, 2013;Cuomo et al, 2017;Kiran et al, 2017;Schwessinger et al, 2018;Xu et al, 2020). This genetic characteristic results in rapid emergence of virulent Pst races.…”
Section: Introductionmentioning
confidence: 99%
“…This pathogen possesses the ability to generate several resistance-breaking races or pathotypes that carry different race-specific avirulence or effector coding genes that make them more specialized in infecting different wheat cultivars. Pst genomes are highly heterozygous and encode several effectors (Chen et al, 2009(Chen et al, , 2010Cantu et al, 2013;Zheng et al, 2013;Cuomo et al, 2017;Kiran et al, 2017;Schwessinger et al, 2018;Xu et al, 2020). This genetic characteristic results in rapid emergence of virulent Pst races.…”
Section: Introductionmentioning
confidence: 99%
“…tritici, Pst), stem rust (Puccinia graminis f. sp. tritici, Pgt), and leaf rust (Cantu et al, 2011;Duplessis et al, 2011;Zheng et al, 2013;Kiran et al, 2016;Xu et al, 2020). The draft genome of the wheat leaf rust fungus has greatly facilitated efforts to identify genes associated with leaf rust infection (Kiran et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies, PEC6, Pst_8713, PstGSRE1, and PSTha5a23 have demonstrated suppression of plant PTI and ETI as a type of effector proteins of Pst (22)(23)(24)(25). Sixty-nine of 91 haustorial secreted proteins of Pst have been proved to suppress PCD in tobacco (53). Moreover, it has been proved that effectors of bacteria, oomycetes, and fungi can suppress PTI-associated PCD and callose deposition, as well as ETI-associated ROS accumulation (22,26,54,55).…”
Section: Discussionmentioning
confidence: 98%